2020
DOI: 10.3390/children7120258
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence against Children and Adolescents Taking Place in Schools: An Integrative Review

Abstract: Sexual violence against children and adolescents is considered a public health problem of worldwide scope. The objective is to analyze the findings in the literature that address the phenomenon of sexual violence against children and adolescents in the school environment; is an integrative literature review that has as its element-problem of interest children and adolescent victims of sexual violence in schools. The research filters used were: the availability of the text (free full text) and publication date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous studies found that choosing transformative interactions helps in identifying violence situations, placing value on support and friendship, and promoting the helpful role of allies [37,38]. Research has already demonstrated that one factor related to the occurrence of sexual violence against children and adolescence in the school context is the lack of educational interventions on this topic [39]. In this regard, educative and health interventions with adolescents that promote a critical analysis of the coercive dominant discourse can have a transformative effect [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that choosing transformative interactions helps in identifying violence situations, placing value on support and friendship, and promoting the helpful role of allies [37,38]. Research has already demonstrated that one factor related to the occurrence of sexual violence against children and adolescence in the school context is the lack of educational interventions on this topic [39]. In this regard, educative and health interventions with adolescents that promote a critical analysis of the coercive dominant discourse can have a transformative effect [15].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil the past studies show that sexual violence against children was related to school structure and lack of discussion on the subject matter (Pereira et al, 2020). Similarly, in Indonesia, the study found that the root causes of sexual violence against children were family disharmony, religious values, uncomfortable environment, technology and internet and lack of education (Rosyadi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another form of VAC which has prompted considerable attention within the scientific community is that of child sexual abuse (CSA). The numerous studies available show that CSA is present in diverse settings, including homes [6,7], schools [8,9], religious institutions [10], and broader communities [11]. The most prevalent context for children to encounter physical and emotional violence is typically within their own homes [12,13].…”
Section: Introductionmentioning
confidence: 99%